Forgiveness in Psychotherapy: The Key to Healing. Issue 8 (17th June 2013) - Menahem, Sam; Love, Melanie
<x xml:space="preserve">Abstract</x> The process of forgiveness in psychotherapy involves both letting go of resentment toward the offender and replacing the resentment with mindful awareness and empathy. By reconceptualizing past transgressions with a kinder, more equivocal outlook, clients attain a shift in perspective that is spiritual and cognitive in nature, thereby reducing symptomology and enhancing their quality of life. Such insights bring clients toward their inner Buddha nature, which transcends the suffering associated with clinging to past hurts and resentment. This process is facilitated by techniques such as concentrative meditation and identifying with transgressors through perspective taking. Forgiveness therapy improves clients' sense of well‐being by promoting feelings of peacefullness toward oneself as well as others.